2012
DOI: 10.3892/ijmm.2012.1156
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate restores ASC expression and induces apoptosis in LS174T cells

Abstract: Abstract. Sodium butyrate (NaBu) is a short-chain fatty acid (SCFA), which has been proposed as a potential anticancer agent. Apoptosis-associated speck-like protein (ASC) is a pro-apoptotic signaling factor that is subjected to epigenetic silencing in human cancers. Modulation by the aberrant methylation of CpG islands of ASC is a well-characterized epigenetic mechanism, and the methylation-induced silencing of ASC has been observed in several types of tumors. NaBu induces cell cycle arrest, markers of cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…This dose-dependency effect is congruent with the outcome observed in previous experiments and with other inhibitors and pharmacological treatments [19,20]. The results also demonstrate that low, but not higher, doses of NaBu (10 mg/0.5 ml) had an effect on aversive memory extinction, indicating that the NaBu effect is dose-dependent and the inhibitory activity could be mediated by low concentrations that particularly affect histone deacetylation.…”
Section: Discussionsupporting
confidence: 90%
“…This dose-dependency effect is congruent with the outcome observed in previous experiments and with other inhibitors and pharmacological treatments [19,20]. The results also demonstrate that low, but not higher, doses of NaBu (10 mg/0.5 ml) had an effect on aversive memory extinction, indicating that the NaBu effect is dose-dependent and the inhibitory activity could be mediated by low concentrations that particularly affect histone deacetylation.…”
Section: Discussionsupporting
confidence: 90%
“…Butyrate induces a minimal apoptotic and necrotic effect on MG-63 cells as analyzed by propidium iodide (PI) and annexin V flow cytometry. Other studies have reported the induction of apoptosis on colon cancer cells, B cells and other kinds of cells by butyrate [1,24,25], showing the effect of butyrate may vary by cell type. Ho & Chang (2007) further discovered the toxicity of butyrate on dental pulp cells and its relation to glutathione (GSH) depletion [26].…”
Section: Discussionmentioning
confidence: 99%
“…While mesenchymal stem cells are known to become flattened, spread and to differentiate into osteoblasts [50], butyrate is shown to affect the differentiation of colon cancer cells and osteoblastic cells [1,24,49,51]. Butyrate (0.1 mM) stimulates the expression of mineralization markers in periodontal ligament cells, whereas butyrate exhibits cytotoxicity at concentrations higher than 1 mM [52].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies demonstrated butyrate had anti-CRC activity associated with prevention of DNA methylation. For example, in LS174T colon cancer cells, butyrate decreased cell proliferation and rescued apoptosis-associated speck-like protein (ASC), a proapoptotic protein silenced by DNA methylation in CRC ( 151 ). In HT-29 colon cancer cells, butyrate was found to protect against genotoxicity induced by the secondary bile DCA ( 152 ), and lower DNMT1 levels ( 153 ).…”
Section: Discussionmentioning
confidence: 99%